Erythrocyte Shape Abnormalities, Membrane Oxidative Damage, and β-Actin Alterations: An Unrecognized Triad in Classical Autism. (21st December 2013) - Ciccoli, Lucia; De Felice, Claudio; Paccagnini, Eugenio; Leoncini, Silvia; Pecorelli, Alessandra; Signorini, Cinzia; Belmonte, Giuseppe; Guerranti, Roberto; Cortelazzo, Alessio; Gentile, Mariangela; Zollo, Gloria; Durand, Thierry; et al.
Abstract : Autism spectrum disorders (ASDs) are a complex group of neurodevelopment disorders steadily rising in frequency and treatment refractory, where the search for biological markers is of paramount importance. Although red blood cells (RBCs) membrane lipidomics and rheological variables have been reported to be altered, with some suggestions indicating an increased lipid peroxidation in the erythrocyte membrane, to date no information exists on how the oxidative membrane damage may affect cytoskeletal membrane proteins and, ultimately, RBCs shape in autism. Here, we investigated RBC morphology by scanning electron microscopy in patients with classical autism, that is, the predominant ASDs phenotype (age range: 6–26 years), nonautistic neurodevelopmental disorders (i.e., "positive controls"), and healthy controls (i.e., "negative controls"). A high percentage of altered RBCs shapes, predominantly elliptocytes, was observed in autistic patients, but not in both control groups. The RBCs altered morphology in autistic subjects was related to increased erythrocyte membrane F2 -isoprostanes and 4-hydroxynonenal protein adducts. In addition, an oxidative damage of the erythrocyte membrane β -actin protein was evidenced. Therefore, the combination of erythrocyte shape abnormalities, erythrocyte membrane oxidative damage, and β -actin alterations constitutes a previously unrecognized triad in classical autism and provides new biological markers in the diagnostic workup of ASDs.